GOVERNMENT ACCOUNTING COMPETENCY IMPROVEMENT FOR TEACHERS - Dani Sugiri; Budi Mulyana; Tanda Setiya (JCES (Journal of Character Education Society), 2021)
Abstrak: Kegiatan peningkatan kompetensi akuntansi instansi pemerintah bertujuan membantu guru akuntansi yang tergabung dalam MGMP Kabupaten Lebak. Para guru mengalami kesulitan dalam memahami dan menyampaikan materi mata pelajaran akuntansi instansi pemerintah. Kegiatan dilaksanakan dalam bentuk pelatihan selama tiga hari untuk guru akuntansi sebanyak 30 orang. Materi pelatihan berisi mengenai konsep pengelolaan keuangan daerah, konsep akuntansi pemerintah daerah serta praktik akuntansi instansi pemerintah daerah. Kegiatan pelatihan juga diisi dengan microteaching bagi peserta pelatihan dan diskusi mengenai kendala pengajaran laboratorium akuntansi instansi pemerintah daerah di lingkup SMK pada Kabupaten Lebak. Kegiatan ini menghasilkan peningkatan kemampuan peserta dalam memahami dan menyelesaikan tiga kasus akuntansi pemerintah daerah yang dapat digunakan sebagai bahan pengajaran di kelas. Kegiatan ini juga dapat merumuskan beberapa kebutuhan penyesuaian kurikulum dan bahan ajar mata pelajaran akuntansi instansi pemerintah di lingkup SMK Kabupaten Lebak.Abstract: Activities to increase the accounting competence of government agencies aim to assist accounting teachers who are members of the MGMP of Lebak Regency. Teachers have difficulty understanding and delivering government agency accounting subject matter. Activities carried out in the form of training for three days for accounting teachers as many as 30 people. The training material contains regional financial management concepts, local government accounting concepts and accounting practices of local government agencies. The training activities were also filled with microteaching for training participants and discussions about the constraints of teaching accounting laboratories of local government agencies in the scope of SMK in Lebak Regency. This activity resulted in an increase in the ability of participants to understand and solve three accounting cases in SKPD that could be used as classroom teaching materials. This activity can also formulate some needs for curriculum adjustments and teaching materials for government agencies in the scope of SMK in Lebak Regency.